2013
DOI: 10.1001/2013.jamainternmed.1013
|View full text |Cite
|
Sign up to set email alerts
|

Patient Knowledge and Understanding of Radiation From Diagnostic Imaging

Abstract: ested in increasing the use of generic drugs may consider banning physicians from accepting food and beverages in the workplace. Any potential interventions should be targeted toward older physicians, internists, and those in solo or 2-person practices.Our study has several limitations. First, because of social desirability bias, our results likely represent a lowerbound estimate of the actual frequency of physicians prescribing brand-name drugs at the patients' requests. Second, we were unable to adjust the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 7 publications
3
35
0
1
Order By: Relevance
“…Nonetheless, patient knowledge regarding the examinations involving ionizing radiation was variable and generally poor. As in other studies (9,10), very few participants had ever discussed their concerns with a health care provider, relying on information from self-directed internet searches instead. The amount and type of information each participant wanted about imaging tests was extremely variable.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Nonetheless, patient knowledge regarding the examinations involving ionizing radiation was variable and generally poor. As in other studies (9,10), very few participants had ever discussed their concerns with a health care provider, relying on information from self-directed internet searches instead. The amount and type of information each participant wanted about imaging tests was extremely variable.…”
Section: Discussionmentioning
confidence: 92%
“…Although we discovered many reasons a patient with cancer may not seek information about the risks of ionizing radiation from imaging, study participants clearly believed such information should be routinely available to patients. Similarly, Busey et al (10) found that 90% of patients felt that it was important to be informed of imaging risks. The transition to survivorship prompted increased concern about the risks of ionizing radiation from medical imaging among our participants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies reported that patients have a poor understanding of the ionizing radiation exposure associated with CT and that potential risks are rarely communicated to them. 14,24 We found that approximately one-quarter of emergency physicians reported having been asked by their patients about the risks of malignancy due to CT imaging and that one-third communicated these potential risks to their patients most of the time. These rates are comparable to previous studies in which rates of 22 to 40% were reported for regular emergency medicine physician communication of these risks.…”
Section: Discussionmentioning
confidence: 96%
“…Another recently published survey of patients presenting for nonurgent outpatient CT and cardiac single-photon emission CT scans revealed that 90% said that it was important to be informed of imaging risks [40]. In yet another survey of parents who brought their children who had sustained head injuries to a hospital emergency department, 90% wanted to be informed of potential malignancy risks before proceeding with CT scans [41].…”
Section: Legal Duty Moral Duty and Shared Decision Makingmentioning
confidence: 99%